Hepatoprotective Effects of Astaxanthin Against Diazinon-Induced Cardiotoxicity in Rats: Efek Hepatoprotektif Astaxanthin Terhadap Kardiotoksisitas yang Diinduksi Diazinon pada Tikus - Razzaq, Fatimah Riyad Abdul; Al-Darraji, Ahmed H. (Academia Open, 2025)
Background: Astaxanthin, a marine-derived carotenoid, possesses potent antioxidant and anti-inflammatory properties with potential therapeutic effects in liver diseases. Specific Background: Diazinon, a widely used organophosphorus pesticide, induces hepatotoxicity through oxidative stress and inflammation. Knowledge Gap: Although astaxanthin’s antioxidant potential is recognized, its protective role against diazinon-induced liver injury remains underexplored. Aim: This study investigated the hepatoprotective effects of astaxanthin against diazinon-induced liver toxicity in male rats. Results: Thirty rats were divided into five groups and treated with diazinon alone or in combination with astaxanthin (50 mg/kg and 100 mg/kg), vitamin C, or distilled water for 30 days. Diazinon exposure significantly elevated serum ALT, AST, and IL-1β levels, reduced hepatic GPx activity, and caused histopathological liver damage. Astaxanthin pre-treatment, particularly at 100 mg/kg, significantly attenuated these effects by normalizing enzyme levels, reducing inflammatory markers, enhancing antioxidant activity, and preserving liver histology. Novelty: This study is among the first to demonstrate astaxanthin’s dose-dependent hepatoprotective effect against organophosphate-induced toxicity. Implications: Astaxanthin shows promise as a therapeutic agent for mitigating liver damage caused by environmental toxins, warranting further clinical and mechanistic investigations. Highlights: Astaxanthin lowers AST, ALT, IL-1β in treated rats. Liver histology improved with astaxanthin pre-treatment. Shows promise as hepatoprotective agent against diazinon toxicity. Keywords: Diazinon, Astaxanthin, vitamin C, Antioxidants, hepatotoxicity